Tawakkul: exemplary deeds of the mother and the sister of prophet Mūsā - Bahari, Che Amnah (IIUM Press, International Islamic University Malaysia, 2019)
Tawakkul or reliance on God has a strong relationship with īmān (faith) in Him. It also refers to taqwā or God consciousness. Al-Qur’ān for that matter has stipulated success depends on one’s complete reliance on Him, steadfast in obeying and fulfilling all the commandments postulated by Him. This would mean that tawakkul requires the essential steps needed to achieve the goals and so the act of striving for the goals is an act of submission while believing and reliant on God is faith in Him. This paper attempts to study Qur’ānic approach to tawakkul in connection with the uncertainties faced by the mother and sister of Prophet Mūsā to protect baby Mūsā from evil deeds of Firʽaūn. It also discusses the good-natured actions applied by them to overcome their fears. This paper ends by explaining the relevancy of practicing the correct method of tawakkul and the impact on wellbeing of mind.